2017
DOI: 10.1134/s1607672917040081
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic changes in tumor-associated macrophages during cancer grow in mice with Ehrlich ascites carcinoma

Abstract: In this work, we investigated the activity of the key NAD(P)-dependent dehydrogenases associated with macrophage tumors in mice with Ehrlich ascites carcinoma. It was shown that cancer grow is associated with the development of conditions in macrophages leading to a decrease in the substrate flow intensity in the tricarboxylic acid cycle, deceleration of oxidative deamination of L-glutamate, NADP regeneration, and a decrease in the antioxidant defense efficiency. There results are consistent with our recent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Inzhevatkin et al reported the suppression of metabolic processes of macrophages that were associated with tumors during tumor growth. Neutrophils are another important cell population in tumor development ( 32 ). AEC plays a paradoxical dual role in these cells, in which neutrophils are responsible for controlling tumor development in susceptible animals (e.g., Swiss mice), but in mice that are resistant to tumor development [e.g., CAF1 (BALB/c A/J) F1 mice], neutrophils improve tumor growth ( 33 ).…”
Section: Immune and Systemic Alterations Caused By Ehrlich Tumorsmentioning
confidence: 99%
“…Inzhevatkin et al reported the suppression of metabolic processes of macrophages that were associated with tumors during tumor growth. Neutrophils are another important cell population in tumor development ( 32 ). AEC plays a paradoxical dual role in these cells, in which neutrophils are responsible for controlling tumor development in susceptible animals (e.g., Swiss mice), but in mice that are resistant to tumor development [e.g., CAF1 (BALB/c A/J) F1 mice], neutrophils improve tumor growth ( 33 ).…”
Section: Immune and Systemic Alterations Caused By Ehrlich Tumorsmentioning
confidence: 99%